Difference in Therapeutic Strategies for Joint‐Preserving Surgery for Non‐Traumatic Osteonecrosis of the Femoral Head between the United States and Japan: A Review of the Literature. Issue 3 (5th April 2021) - Kuroda, Yutaka; Okuzu, Yaichiro; Kawai, Toshiyuki; Goto, Koji; Matsuda, Shuichi
Abstract : For patients with non‐traumatic osteonecrosis of the femoral head (ONFH), core decompression (CD) and bone grafts (BG) are mainly performed in the West, while osteotomy is found to be predominant in Japan. It is not well recognized how the surgical procedures for joint preservation in patients with ONFH are completely different between the United States and Japan. This paper identifies the contexts and the differences in treatment strategies for ONFH between the two countries. We compared the surgical trends of the two countries over three periods, 1997–2001, 2002–2006, and 2007–2011 (the US data for the third period was 2007–2008), based on a 2014 US paper and a 2013 national publication in Japan. We compared the details of surgery for non‐traumatic ONFH under the same conditions in the two reports. For the period 1997–2001, the rates of surgeries for ONFH in the US were as follows: total hip arthroplasty (THA), 86%; CD, 10%; and osteotomy, 0.4%. In Japan, THA was 61%, osteotomy 38%, and CD 0%. For the recent period, 2007–2011 (US 2007–2008), the rate of THA was 91%, CD 6%, and osteotomy 0.1%, in the US, compared to a THA rate of 73%, CD 0%, and osteotomy 26% in Japan. The results for the interim period (2002–2006) were between the old and new data. The use of joint‐preserving surgery for ONFH differs greatly between the US and Japan. The first‐line joint‐preserving surgery was CD in the US and osteotomy in Japan. Each procedure was rarely done in the other country. From about 2000 to 2010, the percentage of THA increased in both countries. The proportion of joint‐preserving surgery (CD in the US and osteotomy in Japan) declined. The decrease in joint‐preserving procedures may be largely attributed to improved long‐term outcomes of THA due to technological advances. There is also a reluctance for young ONFH patients to undergo joint‐preserving procedures, such as osteotomy, that require long‐term hospitalization. Abstract : A comparison of the ONFH procedures between 2000 and 2010 in the US and Japan showed that the use of joint‐preserving techniques was very different. First‐line joint‐preserving surgery is CD in the US, while it is osteotomy in Japan. Each country rarely performed the alternative technique.